Free Will: A consensus gentium Argument - William Hunt (Organon F, 2024)
This argument for free will is a probabilistic one based upon two conjectures: first, that of consensus; namely, that a large majority of people believe that they and others have free will and second, that a priori proofs against the existence of free will either fail or remain questionable. If these two conjectures hold, an inductive argument follows on the basis of beliefs founded upon justified auxiliary assumptions, assumptions that ensure a well-defined probabilistic relationship between the evidence of consensus and the proposition free will exists in an elaborated form. I will then demonstrate, through subjective Bayesian confirmation theory, that such evidence probabilistically confirms this proposition. Moreover, if one’s prior degree of belief in the existence of free will is not very low - prior that is to consideration of the evidence - then, provided this evidence is factual, it is likely that one’s resultant degree of belief in the veracity of the proposition is not only rational, but also compelling.